Irrigation Network Information System in Karo Regency - Wira Pratama; Achwil Putra Munir; Saipul Bahri Daulay (Universitas Sumatera Utara, 2013)
Information system in Karo Regency irrigation area was still done manually, so the storage, processing and delivery of information to be ineffective and inefficient. In the information management most the result were done by human role and took a relatively longer time. Moreover, the information seekers-and decision-makers also had difficulty in obtaining the data they need. Therefore, it is necessary to further develop of the information system. Web-based information system is considered to be a solution in order to access information faster, systematicaly and easy to use. For that a web-based information systems in the management of irrigation in Karo Regency irrigation area was designed. Irrigation network information system was designed using PHP programming language, MySQL database and the method of system development life cycle (SDLC). The result was adynamic website that displays information and could interact with the user and was user friendly where the model user interface of the web was made to facilitate the user to use system properly. Keywords: information system, irrigation system, Karo Regency irrigation area, web